Pengaruh Mentor dalam Mengurangi Loneliness pada Mahasiswa Angkatan 2023 di Sekolah Tinggi Teologi Ekumene Jakarta Yang Tinggal di Asrama - Priska Oktaviani Zai (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine how big the relationship between the influence of mentors in reducing loneliness for students living in the dormitory of the Jakarta Ecumenical Theological College. This study uses quantitative research methodology and uses a survey research design. This study has a population of 110 people with a sample size of 84 people consisting of students living in dormitories. This study uses the Isaac and Michael table with a 5% error rate. In this study, researchers collected data by distributing questionnaires in the form of questionnaires and this data was analyzed using computer programs, namely Ms. Excel and SPSS 20.0 for windows. Based on the results of the hypothesis test that the researcher has conducted, this study shows that there is a significant relationship between the influence of loneliness in reducing loneliness experienced by students living in dormitories with the results of the linear regression test of 55.2% with an r square of 0.552. This can indicate that there is an influence of mentors in reducing loneliness in students of the Jakarta Ecumenical Theological College who live in dormitories.